2022
DOI: 10.1186/s41983-022-00528-z
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic stroke in COVID-19 patients: a cross-sectional study from an Indonesian COVID-19 referral hospital

Abstract: Background COVID-19 increases the risk of acute ischemic stroke. The objective of this study is to identify the risk factors, comorbidities, and outcomes in COVID-19 patients with acute ischemic stroke at University of Indonesia Hospital. Results The clinical condition of COVID-19 patients with ischemic stroke is more severe for patients older than 55 years (p < 0.05), patients at the critical COVID-19 clinical stage, and patients with atrial fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
2
0
1
Order By: Relevance
“…10 This is supported by research by Hidayat et al who reported an increase in D-dimer in 98.1% of stroke patients at the University of Indonesia Hospital. 11 In our study, the mean and median D-dimer were 5.36 mg/mL and 2.36 mg/mL, respectively, well above the normal value of 0.55 mg/mL. Yaghi et al in a New York study found similar results, confirming D-dimer with a median of 3.91 mg/mL in acute ischemic stroke patients with COVID-19.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…10 This is supported by research by Hidayat et al who reported an increase in D-dimer in 98.1% of stroke patients at the University of Indonesia Hospital. 11 In our study, the mean and median D-dimer were 5.36 mg/mL and 2.36 mg/mL, respectively, well above the normal value of 0.55 mg/mL. Yaghi et al in a New York study found similar results, confirming D-dimer with a median of 3.91 mg/mL in acute ischemic stroke patients with COVID-19.…”
Section: Discussionsupporting
confidence: 84%
“… 10 This is supported by research by Hidayat et al who reported an increase in D-dimer in 98.1% of stroke patients at the University of Indonesia Hospital. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Angka mortalitas dari pasien lansia pada penelitian sebelumnya (>65 tahun) yakni memiliki nilai risk ratio sebesar 62.1 (62 kali lebih berisiko terkena stroke iskemik). 7 Pada penelitian sebelumnya, didapatkan pasien lansia memiliki risiko lebih tinggi untuk terkena stroke iskemik dikarenakan faktor risiko yang mengasosiasi terjadinya stroke seperti atrial fibrilasi, skor NIHSS (National institutes of health stroke scale) tinggi, dan angka rawat inap lebih tinggi pada pasien lansia. Pasien lansia dengan stroke iskemik lebih sering disebabkan oleh kardioemboli, hal ini dikarenakan tingginya faktor risiko atrial fibrilasi pada pasien lansia.…”
Section: Pembahasanunclassified
“…6 A recent study on COVID-19-positive patients with ischemic stroke at the University of Indonesia Hospital in Depok found that the majority of patients are over the age of 55. 7 Several clinical studies showed that blood laboratory examinations may be correlated to a patient's prognosis. An increased white blood cell (WBC) count on admission has been correlated with increased mortality in stroke patients and could be used as a risk factor marker.…”
Section: Introductionmentioning
confidence: 99%